Blended Concessional Finance : The Benefits of Transparency and Access - Karlin, Arthur (International Finance Corporation, Washington, DC, 2021)
Blended concessional finance, the combination of commercial finance from the private sector and development finance institutions (DFIs) with concessional finance from public and other sources, is increasingly being used by DFIs to support developmentally important projects where normal DFI or commercial finance is not available because of the high risks involved. This can be especially significant in lower-income and fragile and conflict-affected situations (FCS), where risks are high and innovative and pioneering projects can be critical to economic growth, market creation, and poverty reduction. Blended concessional finance is also being used during the COVID-19 pandemic to help sustain struggling businesses hurt by demand and supply shocks, and to rebuild economies toward green, resilient, and inclusive growth. As blended concessional finance involves the use of concessional public or philanthropic1 funds to enhance the viability of private sector projects, strong processes, particularly in the areas of transparency, access, and governance, are necessary to ensure that these resources are used effectively and without distorting markets.